2021
DOI: 10.5045/br.2021.2020334
|View full text |Cite
|
Sign up to set email alerts
|

The clinical role of interferon alpha in Philadelphia-negative myeloproliferative neoplasms

Abstract: Myeloproliferative neoplasms (MPNs) are clonal hematopoietic stem cell malignancies. Chronic inflammation and a dysregulated immune system are central to the pathogenesis and progression of MPNs. Interferon alpha (IFNα) was first used for the treatment of MPNs approximately 40 years ago. It has significant antiviral effects and plays a role in anti-proliferative, pro-apoptotic, and immunomodulatory responses. IFNα is an effective drug that can simultaneously induce significant rates of clinical, hematological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Since the introduction of pegylated (PEG)-IFNa, which reduces both dosing intervals and side-effects compared with the non-pegylated form, IFNa has regained interest as a potential tool to interfere with the disease course, via potently inducing hematologic and molecular responses in a majority of ET and PV patients [ 87 ]. In MF patients, the overall response rate (ORR) is lower than in ET or PV patients, and complete responses are rare [ 89 ]. In this subtype, combination treatments with ruxolitinib may achieve better results [ 90 , 91 ].…”
Section: Novel Therapeutics Targeting Mpn Progressionmentioning
confidence: 99%
“…Since the introduction of pegylated (PEG)-IFNa, which reduces both dosing intervals and side-effects compared with the non-pegylated form, IFNa has regained interest as a potential tool to interfere with the disease course, via potently inducing hematologic and molecular responses in a majority of ET and PV patients [ 87 ]. In MF patients, the overall response rate (ORR) is lower than in ET or PV patients, and complete responses are rare [ 89 ]. In this subtype, combination treatments with ruxolitinib may achieve better results [ 90 , 91 ].…”
Section: Novel Therapeutics Targeting Mpn Progressionmentioning
confidence: 99%
“…Efficacy evaluation criteria were referred to the prior literature [ 9 ]. Progression-free survival (PFS) refers to the duration from the date of enrollment to the first occurrence of disease progression (new thrombosis, bleeding events, progressive enlargement of the spleen, myelodysplastic syndrome (MDS), myelofibrosis (MF), aggravation of the original myelofibrosis reticulum staining, or acute myeloid leukemia (AML) caused by peripheral cytopenia), or from the date of enrollment to the time of death from any cause.…”
Section: Methodsmentioning
confidence: 99%
“…To capture these symptoms directly from patients with MPNs, the Myelofibrosis Symptom Assessment Form was developed, which was subsequently modified to include ET and PV to form the Myeloproliferative Neoplasm Symptom Assessment Form (MPN-SAF) [ 24 , 25 ]. Numerous studies have shown that ruxolitinib and interferon (IFN) are effective in the symptomatic management of patients with MPNs [ 26 , 27 ]. Complete responses were obtained in patients with PV and ET who were treated with either hydroxyurea (HU) or pegylated interferon alfa-2a (peg IFNα-2a); however, only 19–32% of the patients reported clinically significant improvement in symptom reduction [ 28 ].…”
Section: Unmet Needs In Current Pv/et Treatmentmentioning
confidence: 99%
“…With the development of peg IFNα-2a and ropeg IFNα-2b, side effects have been reduced and administration intervals have been extended. Therefore, IFN is a promising treatment of choice for disease modification, especially given its impact on mutation burden [ 27 ].…”
Section: Novel Agents For Pv/et Treatmentmentioning
confidence: 99%